From Goethe to Gundolf : Essays on German Literature and Culture. - Paulin, Roger. (Open Book Publishers, 2021)
From Goethe to Gundolf: Essays on German Literature and Culture is a collection of Roger Paulin's groundbreaking essays, spanning the last forty years. The work represents his major research interests of Romanticism and the reception of Shakespeare in Germany, but also explores a broader range of themes, from poetry and the public memorialization of poets to fairy stories - all meticulously researched, yet highly accessible.